`(root(4)(16+h)-2)/h`

function `f(x)=root(4)(x)`

evaluate at a=16

`f(16+h)=root(4)(16+h)`

`f(16)=root(4)(16)=2`

`(f(16+h)-f(16))/h=(root(4)(16+h)-2)/h`

So the answer is `f(x)=root(4)(x)` and `a=16`

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now